Genetic Diversity Evaluation of Sugarcane Clones Using Multivariate Analysis - Padmavathi, P. V.; Adilakshmi, D.; Rao, D Purushotama; Ch. Mukunda Rao, (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during the 2022–2023 crop season (March, 2022 to May, 2023) at the Regional Agricultural Research Station (RARS), Anakapalle, Andhra Pradesh, to study the genetic variability among sugarcane (Saccharum spp.) clones for key agronomic and quality traits and to identify superior genotypes for breeding. A total of 130 sugarcane clones were evaluated using an augmented block design. Genetic variance analysis revealed significant variation for single cane weight, though other traits showed non-significant variance, possibly due to environmental consistency or design constraints. High genotypic and phenotypic coefficients of variation (GCV and PCV) were observed for number of millable canes, single cane weight, Brix (%), and sucrose (%), while juice purity exhibited low variability. Stalk length and girth displayed moderate genetic variation. All traits showed high broad-sense heritability, with high genetic advance except for juice purity. Cluster analysis categorized the 132 clones into four groups, with Cluster 4 (69 clones) being the largest and Cluster 2 (7 clones) the smallest. Principal Component Analysis (PCA) retained the first three components (eigenvalues≥1), explaining 76.7% of total variation. PC1 (eigenvalue 2.494) accounted for 35.6% of variability, tied to juice quality traits. PC2 (eigenvalue 1.831) explained 26.2%, linked to stalk length and girth, while PC3 (eigenvalue 1.046) captured 14.9%, influenced by millable canes and stalk length. This study underscores PCA’s value in identifying key traits for genetic variability, aiding breeding efforts. Future work should incorporate multi-location trials and molecular markers to enhance selection precision and identify stable, high-yielding clones.